Two-level model of composite synthesis on a substrate from a powder mixture of TIO2 and AL. 1. Model description and simple examples; Nanoscience and Technology: An International Journal; Vol. 14, iss. 3 - Knyazeva A. G. Anna Georgievna (2023, 2023)
Title screen